SREBP1c silencing reduces endoplasmic reticulum stress and related apoptosis in oleic acid induced lipid accumulation - SÖZEN, AHMET ERDİ; KARTAL ÖZER, NESRİN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Sterol regulatory element binding protein 1c (SREBP1c) is one of the major transcription factors that is involved in non-alcoholic fatty liver disease (NAFLD) development by increasing hepatic fatty acid and triglyceride synthesis. Our study aimed to investigate the interaction of SREBP1c with endoplasmic reticulum (ER) stress in oleic acid (OA) induced lipid accumulation. Material and Methods: Optimum lipid droplet (LD) formation and SREBP-1c induction were determined in alpha mouse liver 12 (AML12) hepatocytes following the incubation with different OA concentrations. To determine the effect of SREBP-1c, cells were transfected with siRNA specific for SREBP-1c. LD formation and SREBP-1c induction were determined via Oil Red O and immunblotting, respectively. Phospho IRE1, GRP78, CHOP, ATF6 and JNK levels were determined with immunofluorescence staining. Results: Optimum LD formation and SREBP-1c induction were achieved at 0.5 mM oleat concentration. While SREBP-1c silencing decreased LD formation in non-OA treated cells, no significant effect of silencing was determined following OA administration. On the other hand, SREBP-1c silencing in OA treated cells reduced phospho IRE1, ATF6, JNK and CHOP expressions. Conclusion: Our results suggest that the novel function of SREBP-1c can regulate ER stress response in OA induced lipid accumulation.
Keywords: Lipid accumulation; SREBP1c; ER stress; Apoptosis; DE-NOVO LIPOGENESIS; ER STRESS; INSULIN ACTION; IN-VITRO; LIVER; STEATOSIS; ACTIVATION; MECHANISMS; PATHOGENESIS; EXPRESSION